ЩОДО ПРОБЛЕМИ КОНКУРЕНТОЗДАТНОСТІ ФАХІВЦІВ - Бикова, Вікторія (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті на підставі аналізу наукової літератури презентоване авторське бачення сутності феномену конкурентоздатність фахівця, який визначено як складну, багаторівневу інтегральну властивість, яка дозволяє особистості відповідно до її індивідуальних властивостей, потреб, прагнень брати участь і отримувати переваги в конкурентних відносинах в обраній сфері професійної діяльності. Визначено структурні компоненти конкурентоздатності фахівця (аксіологічний, когнітивний, особистісний, професійний). В статье на основании анализа научной литературы представлено авторское видение сущности феномена «конкурентоспособность специалиста», который определен как сложное, многоуровневое интегральное свойство, которое позволяет личности в соответствии с ее индивидуальными свойствами, потребностями, стремлениями участвовать и получать преимущества в конкурентных отношениях в выбранной сфере профессиональной деятельности. Определены структурные компоненты конкурентоспособности специалиста (аксиологический, когнитивный, личностный, профессиональный). The article is based on an analysis of scientific literature presented copyright vision of the phenomenon of competitive expert. The phenomenon is defined as a complex, multi-level integral feature that allows person in accordance with its individual characteristics, needs, and desire to participate and receive benefits in a competitive relationship in chosen professional field. The author determines the competitive expert as a person focused on the success, enrichment of knowledge and their application in professional activities, updating professional experience, creative expression, with achievement need; who differs by autonomy of decision-making and actions, by developed emotional intelligence, by ability to adapt in professional competitive environment, adequate assessment of reality, by the reflection of his own activities. The structural components of competitiveness expert consists of axiological (motivation for success / failure, need for achievement, need for independence / autonomy); cognitive (deep knowledge of personal marketing, self-management, branding policy); personal (emotional intelligence, the ability to go for a reasonable risk, commitment and determination); Professional (ability to adapt to the competitive environment, the reflection of their own activities) and its level of formation: low, medium and high. These specifications competitiveness are interdependent and interrelated and provide a successful professional career in the new economy, competitiveness expert on the labor market only by interacting with each other.